2012
DOI: 10.1136/bjsports-2012-091095
|View full text |Cite
|
Sign up to set email alerts
|

Eccentric strengthening effect of hip-adductor training with elastic bands in soccer players: a randomised controlled trial

Abstract: 8 weeks of hip-adduction strength training, using elastic bands, induce a relevant increase in eccentric hip-adduction strength in soccer players, and thus may have implications as a promising approach towards prevention of groin injuries in soccer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
2
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 43 publications
4
53
2
2
Order By: Relevance
“…Exercises in these interventions included concentric and eccentric adductor muscle contractions in coordination with abdominal muscles to target hip adductor weakness 23. We feel that the use of no or minimal equipment, such as elastic bands, progressing into more relevant contraction-specific exercise and positions,57 58 could be more beneficial for hip-adductor strengthening as a preventative measure in male football 24 57…”
Section: Discussionmentioning
confidence: 99%
“…Exercises in these interventions included concentric and eccentric adductor muscle contractions in coordination with abdominal muscles to target hip adductor weakness 23. We feel that the use of no or minimal equipment, such as elastic bands, progressing into more relevant contraction-specific exercise and positions,57 58 could be more beneficial for hip-adductor strengthening as a preventative measure in male football 24 57…”
Section: Discussionmentioning
confidence: 99%
“…The present study included six traditional hip adduction exercises12 15 27 28 and two new exercises which were considered to activate the hip adductor muscle group with a different intensity (figure 1). We wanted to introduce exercises that we thought would represent both high and low intensities, as this can be useful in clinical situations, such as acute versus chronic conditions, where muscle-tendinous structures need to be targeted with different intensities.…”
Section: Methodsmentioning
confidence: 99%
“…Ten repetitions were performed and the relevant load was noted if participants considered the load equivalent to 10 RM. A load of 10 RM is described as heavy resistance training32 and has been used previously in hip adduction strengthening,27 and therefore it is considered as an appropriate reference for exercise comparisons.…”
Section: Methodsmentioning
confidence: 99%
“…A previous study comparing isometric and eccentric hip muscle strength in soccer players showed decreased muscle strength in eccentric hip adduction only in players with hip/groin pain compared with healthy players. 6 In general, eccentric testing produces larger mechanical stress to the muscle-tendon complex and its integrity, 7,12,30,31 and eccentric testing may therefore be more specific to long-standing musculotendinous disorders of the hip than isometric and concentric testing. 30,32 Muscle weakness in long-standing musculotendinous hip pain conditions therefore seems to be more apparent in eccentric tests and thus seem very relevant to measure and quantify.…”
Section: Discussionmentioning
confidence: 99%